The influence of entrepreneurship education and training inbuilding youth entrepreneurial spirit in gorontalo province: - - Andi Mardiana; Eka Zahra Solikahan; Muhammad Ardi; Ansar Sahabi; Abdul Latif (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of the level of education and training in building the entrepreneurial spirit of youth in Gorontalo Province. The research method uses quantitative methods through multiple linear regression analysis, with 350 samples of MSME in Gorontalo Province from 7 fields. The results showed that the R square was 0.315 or 31.5%.From these results, it can be concluded that the level of education and entrepreneurship training that has been taken by young people has a linear correlation with the entrepreneurial spirit they have.This shows that there is a weak relationship between education and training in fostering the entrepreneurial spirit of youth in Gorontalo Province. This is because there are several factors outside the variables studied that can further foster an entrepreneurial spirit. for example environment and e-commerce.